Jacobsen syndrome. Literature review and a case report - A. V. Syrkina; N. V. Chebanenko; V. P. Zykov; N. S. Mikhailova (Русский журнал детской неврологии, 2022)
The article presents a literature review of chromosomal deletion syndrome – terminal deletion of the long arm of chromosome 11, Jacobsen syndrome, manifested by skeletal abnormalities, congenital heart defects, developmental delay, autism. The disease is of clinical interest in connection with a specific phenotype and life-threatening, but potentially curable conditions: bleeding and immunodeficiency. The analysis of informationally significant genes of the chromosome 11 deletion site is presented. A case report of a girl with Jacobsen syndrome with a follow-up history of up to 6 years is presented. In the observed case, previously unremarked symptoms were described: ataxia and retropulsion. The differential diagnosis and criteria for hypomyelination syndrome are also analyzed. Recommendations are given for the management of life-threatening conditions in patients in accordance with American protocols.